A study of historic rural America - Heiman, John (Kansas State University, 2016)
Similar to their urban counterparts, rural communities consider preservation of a site based on their most vital economic features. With the growing minority and non-white cultures becoming more predominant in American society, so too has the culture and significance of historic events changed. More emphasis is now on the surrounding environment of those landmarks historically preserved rather than just the landmarks themselves. And in turn with the environment, more grants and awards are passed down to those sites and locations that provide more options to limiting excess space and energy while utilizing them to the fullest potential. Some conflicts still occur in relation to preserving historical integrity with development, but the total consensus is that historic preservation provides economic benefit more than loss.
Keywords: Rural; Kansas; Historical preservation; Interviews; Architecture; Significance